Development of flavoured milk by adding extracted curcumin from turmeric - Lad, Balaji R; Ingale, Vikramsinh M; Mote, Gurunath G; Wategaonkar, Sandip B; Prathapan, K; Khot, Jayendra A (Journal of Postharvest Technology, 2024)
India's iconic and treasured spice is turmeric. Turmeric known "Indian Saffron" as well. The main  and most effective component of turmeric is curcumin. Turmeric contains a potent plant  component that is thought to have potent anti-inflammatory and antioxidant properties. In this  study, ethanol was used as a solvent to extract curcumin from turmeric. Different concentrations,  including 0%, 25%, 50%, 75%, 85%, and 95%, were used. The ethanol solvent produced a 4.1%  yield at a 95% concentration. Curcumin was characterized and identified using the HPLC  technique, UV spectroscopy, and IR spectroscopy. Milk is an essential food. It provides a variety  of nutrients, including protein, carbohydrates, calcium, vitamins A and B, fats and minerals. For  humans, it is difficult to digest. Full-fat milk cannot be effectively digested by infants or those who  are ill. It is possible to solve these issues by producing flavored milk. Because it is well-liked by  consumers as a refreshing and energizing milk product, flavor milk is quickly becoming an  important part of the market milk sector. Therefore, milk that has been flavor-infused with  curcumin has a unique flavor. Curcumin functions as a flavoring, fragrant, and nutritive substance.  On the basis of sensory and proximal investigation, the F1 sample was chosen. Ash was 0.038%,  fat was 3.1%, and the energy per 100 grams was 74 Kcal. According to the microbiological  investigation, the TPC of the flavored milk increased on the sixth day. So curcumin increased the  shelf life of curcumin..
Keywords: Curcumin; Ethanol,; Extraction,; Flavoured milk; HPLC; IR.